Mini library for Hembusan Kasih Sayang Charity House - Nurull Syamimi, Ahmad Abzan (2017)
Academic Management Division (BPA) has setting up mini library at Hembusan Kasih Sayang Charity House, located in Taman Guru Kuantan, Pahang. This is BPA community service responsibility (CSR) project by donating reading materials to instill reading habits among the orphans who seek shelter at this charity house.